A Novel NF‐κB Inhibitor, Edasalonexent (CAT‐1004), in Development as a Disease‐Modifying Treatment for Patients With Duchenne Muscular Dystrophy: Phase 1 Safety, Pharmacokinetics, and Pharmacodynamics in Adult Subjects. (11th January 2017) - Donovan, Joanne M.; Zimmer, Michael; Offman, Elliot; Grant, Toni; Jirousek, Michael
Abstract: In Duchenne muscular dystrophy (DMD), NF‐κB is activated in skeletal muscle from infancy regardless of the underlying dystrophin mutation and drives inflammation and muscle degeneration while inhibiting muscle regeneration. Edasalonexent (CAT‐1004) is a bifunctional orally administered small molecule that covalently links 2 compounds known to inhibit NF‐κB, salicylic acid and docosahexaenoic acid (DHA). Edasalonexent is designed to inhibit activated NF‐κB upon intracellular cleavage to these bioactive components. Preclinical data demonstrate disease‐modifying activity in DMD animal models. Three placebo‐controlled studies in adult subjects assessed the safety, pharmacokinetics, and pharmacodynamics of single or multiple edasalonexent doses up to 6000 mg. Seventy‐nine adult subjects received edasalonexent, and 25 received placebo. Pharmacokinetic results were consistent with the intracellular cleavage of edasalonexent to its active components. Food increased plasma exposures of edasalonexent and salicyluric acid, an intracellularly formed metabolite of salicylic acid. The NF‐κB pathway and proteosome gene expression profiles in peripheral mononuclear cells were significantly decreased ( P = .02 and P = .002, respectively) after 2 weeks of edasalonexent treatment. NF‐κB activity was inhibited following a single dose of edasalonexent but not by equimolar doses of salicylic acid and DHA. Edasalonexent was well tolerated, and the most common adverse events were mild diarrhea and headache. In first‐in‐human studies, edasalonexent was safe, well tolerated, and inhibited activated NF‐κB pathways, suggesting potential therapeutic utility in DMD regardless of the causative dystrophin mutation, as well as other NF‐κB–mediated diseases.